A new low specific on-resistance Hk-LDMOS with N-poly diode. (January 2017) - Deng, Jing; Huang, Mingmin; Cheng, Junji; Lyu, Xinjiang; Chen, Xingbi
Abstract: A new structure of the laterally diffused metal–oxide–semiconductor transistors (LDMOS) using a high permittivity (H k ) dielectric is proposed, and its mechanism is investigated by 2-D TCAD simulation. The breakdown voltage ( BV ) is remarkably increased by using the H k dielectric. Moreover, a reverse biased poly diode is first introduced on the H k dielectric, which assists the n-drift region forming an electron accumulation layer to reduce the specific on-resistance ( R on, sp ) further. Compared with a conventional LDMOS with the same geometry, the BV increases by 24%, and the R on, sp decreases approximately by 50%. Besides, the proposed structure is less sensitive to the n-drift region doping deviation, and exhibits a larger safe operating area (SOA). Highlights: A 700 V LDMOS structure using a high permittivity (H k ) dielectric is proposed. The breakdown voltage is remarkably increased by using the H k dielectric. An electron accumulation layer is formed at the surface of the drift region.